The international programs of standardized evaluation and the treatment of data at the national level. The case of Argentina in the PISA study of the OECD (Foro de Educacion, 2019)
PISA has become one of the main programs for measuring student performance worldwide. In the last of its editions, in 2015, more than 60 countries participated in the evaluation. The purpose of PISA is to evaluate every three years the performance of students who are completing their compulsory education in three key areas: Reading, Mathematics and Science. As a whole, the information generated is guided by the results of research on the determinants of learning; In this framework, the program distinguishes itself by developing and circulating a broad set of policy recommendations for countries to improve their results. In this regard, recent research showed that PISA has become a material of relevance for the countries, becoming a planning instrument and encouraging the preparation of analyzes, research, documents and government reports (Kotthoff & Pereyra, 2009; Pongratz, 2013). Taking into account this scenario, the article aims to identify the treatment carried out in Argentina of the available data of PISA during the period 2001-2015. For this purpose, it will be investigated in the instrumentation that the national governmental agencies have made on these data, as well as in the media use that has been made in the country on them. It is considered that addressing both issues will contribute to the understanding of the position adopted by the country in the face of these international evaluation programs, considered new governance mechanisms of education on a global scale (Barroso y Carvalho, 2008). Taking into account this scenario, the article aims to identify the treatment carried out in Argentina of the information generated by PISA for the country. For this purpose, the type of instrumentation that national government agencies have carried out on these data is privileged. The analysis is complemented with a brief reference on the media use of PISA in Argentina, especially the written press, in order to glimpse some repercussions and impacts of the evaluation on public opinion. Based on this analysis, it is expected to contribute to the understanding of the position adopted by the country in the face of international evaluation programs such as PISA, which are considered governance mechanisms of education on a global scale (Barroso & Carvalho, 2008).